Pengaruh Solvabilitas dan Likuiditas Terhadap Profitabilitas dengan Nilai Tukar Sebagai Variabel Moderasi - Marcella Puspita; Cahyadi Husadha; Elia Rossa (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2024)
The Effect of Solvency and Liquidity on Profitability with the Exchange Rate as a Moderating Variable (Study of Banking Companies Listed on the Indonesian Stock Exchange for the 2019-2022 Period)". This research aims to examine the effect of solvency and liquidity on profitability with the exchange rate as a moderating variable. This research method uses quantitative methods. The type of data source in this research is the annual financial reports of companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Based on the sampling technique using purposive sampling, a sample of 30 companies was obtained with a research period of 4 years. The analysis technique used is panel data regression. This research uses Eviews software version 12. The results of this research show that: (1) Solvency has no effect on Profitability, (2) Liquidity has no effect on Profitability, (3) Exchange Rates cannot moderate the effect of Solvency on Profitability, (4) The Exchange Rate cannot moderate the influence of Liquidity on Profitability.